The Role Of The Network Operational Automation System Model In Supporting Sustainable Operations In The Telecommunications Industry Of PT. XYZ - Ilyas, Ilyas; Santoso, Sugeng; Imaroh, Tukhas Shilul (International Journal of Indonesian Business Review, 2025)
Purpose – This paper examines the influence of network operational digitalization and network operational automation on sustainable operations, with operational efficiency as a mediating variable. The study was conducted at PT XYZ, a telecommunications company in Indonesia, employing a quantitative approach through a survey of 161 respondents working in network operational units. Methodology/approach – The research instrument was developed based on indicators of digitalization, automation, operational efficiency, and sustainable operations. Data collected were analyzed using Structural Equation Modeling with Partial Least Square (SEM-PLS) through SmartPLS software. Findings – The results reveal that both digitalization and automation of network operations significantly influence operational efficiency. Furthermore, operational efficiency plays a mediating role in linking digitalization and automation to sustainable operations. The study also identifies a significant direct effect of network operational digitalization on sustainable operations. However, network operational automation does not yet demonstrate a direct influence on sustainability outcomes. These findings suggest that while automation contributes to efficiency, its role in sustainability is still evolving, reflecting the staged maturity of technological adoption within the telecommunications industry. Originality/Value – Theoretically, this study contributes to the development of an integrative model connecting digital transformation and sustainable operations in the telecommunications sector. Empirically, it highlights the unique asymmetry between digitalization and automation in driving sustainability, which has been underexplored in prior research. Practically, the results provide valuable insights for company management in formulating effective strategies to enhance digitalization and automation-based network operation systems as a foundation for long-term sustainable operations.